2016
DOI: 10.1080/01904167.2016.1161772
|View full text |Cite
|
Sign up to set email alerts
|

Onion seed productivity, nutrient use, and quality response to drip fertigation in semi-arid India

Abstract: Crop productivity and nutrient use are mainly water restricted in semiarid regions. This study was conducted to find out whether the onion seed crop productivity could be elevated through drip fertigation. The effects of irrigation and fertigation levels on yield, yield components, quality and nutrient use of onion seed crop (Allium cepa L.) were investigated at MPKV Rahuri, western India on a sandy clay loam soil. Irrigation water applied at evapotranspiration (ETc) levels of 80% (I 1 ), 90% (I 2 ) and 100% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Similarly, IM1 significantly improved the WP and NUE by 127.6% and 23.8% than IM2. Unlukara et al (2010) and Dingre et al (2012) supported the study and found that a drip system results in water-savings and increased water use efficiency over surface flood irrigation. As a result, increasing the irrigation water salinity reduced the nutrient uptake up to 47% (N), 21.7% (P), 18.1% (K) as well as the WP by 42%.…”
Section: Resultssupporting
confidence: 54%
“…Similarly, IM1 significantly improved the WP and NUE by 127.6% and 23.8% than IM2. Unlukara et al (2010) and Dingre et al (2012) supported the study and found that a drip system results in water-savings and increased water use efficiency over surface flood irrigation. As a result, increasing the irrigation water salinity reduced the nutrient uptake up to 47% (N), 21.7% (P), 18.1% (K) as well as the WP by 42%.…”
Section: Resultssupporting
confidence: 54%
“…Irrigation was resume two days after SA treatment. Fertigation was applied according to recommended rate only for the first stage of the growth (Dingre et al, 2016). Weed and pest management was carried out as required.…”
Section: Experimental Site and Treatmentsmentioning
confidence: 99%
“…Many studies examined the response of plant to SA under salt stress (Pradhan et al, 2016;Singh andRoy, 2016 andWani et al, 2017). Different plant species at different growth stages influenced differently to abiotic and biotic stress under the effect of SA application (Dingre et al, 2016;El-Katony et al, 2019;Mohammadi et al, 2019 andSingh andRoy, 2016). In addition to the defense mechanism against pathogen, SA play a big role to enhance antioxidant system in the plant, and also regulate cell growth and enlargement (Bhasker et al,2020;Li et al, 2014 andVanacker et al, 2001).…”
Section: Experimental Design Data Collection and Analysismentioning
confidence: 99%